Structure, thermal and fracture mechanical properties of benzoxazine-modified amine-cured DGEBA epoxy resins (eXPRESS Polymer Letters, 2011)
First, traditional diamine hardeners of epoxy resins (EP) were checked as potential accelerators for the benzoxazine (BOX) homopolymerization. It was established that the acceleration effect depends on both the type and amount of the diamine compounds. In the follow-up work amine-curable diglycidyl ether bisphenol A (DGEBA) type EP was modified with BOX keeping the EP/BOX ratio constant (75/25 wt.%). The amine hardeners, added in the EP in stoichiometric amounts, were of aliphatic and aromatic nature, viz. diethylenetriamine (DETA), 4,4'-diaminodiphenyl methane (DDM), and their 1/1 mixture. The thermal, viscoelastic, flexural and fracture mechanical properties of the EP/BOX hybrids were determined and compared to those of the reference EPs. Based on dynamic-mechanical thermal analysis and atomic force microscopy the formation of co-network between EP and BOX was concluded. Homopolymerized BOX was built in the network in nanoscaled inclusions and it was associated with internal antiplasticization. Incorporation of BOX improved the charring, enhanced the flexural modulus and strength, and reduced the glass transition of the parent EP. The fracture toughness and energy were not improved by hybridization with BOX.